Awareness on work stress among public express bus drivers at Terminal Bus Melaka Sentral - Hwang, Fung Chew (Universiti Sains Malaysia, 2012)
Bus drivers are one of several occupational groups who have reported disproportionately high levels of occupational stress. The aims of the research were to study the level of awareness on work stress among public express bus drivers in Melaka and to find the relation between age, education and working experience with awareness level on work stress. A descriptive study on 80 express bus drivers at terminal bus Melaka Sentral was done using a questionnaire. Data was analyzed using the Statistical Package Social Science (SPSS) version 19.0. Majority of the respondents had high level of knowledge on work stress which is 48 (60%) followed by moderate level (32.5%) and only six (7.5%) of the respondents had limited knowledge. Majority of the respondents had positive attitude towards work stress which is 76 (95%). Only 5% of the bus drivers had good practice on work stress. The rest of the respondents (40%) fall in the group of average, followed by the most respondents had bad practice on work stress which is 55%. There is statistically significant relationship between awareness on work stress and education level (p=0.000). There is a significant relationship between awareness on work stress and working experience (p=0.012) too. However, there is no significant between awareness on work stress and age group (p=0.515). In conclusion, the level of awareness on work stress among the express bus drivers in Melaka was high due to their high knowledge level and good practice level on work stress.